1994
DOI: 10.2307/585427
|View full text |Cite
|
Sign up to set email alerts
|

Black Adolescent Females: A Comparison of Early versus Late Coital Initiators

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. National Council on Family Relations is collaborating with JSTOR to digitize, preserve and extend access to Family Relations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Although moderate peer orientation is normative and helps adolescents to establish autonomy as they make the transition to adulthood [19], some youth become excessively peer oriented, to the extent that they abandon family values and personal strengths to gain popularity [20]. Because young people value sexual activity as a sign of maturity [19], peer orientation may be a particularly powerful source of risk in this domain. Indeed, previous research has found peer orientation to be associated with risky sexual attitudes and behavior [21].…”
Section: Youth Mediatorsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although moderate peer orientation is normative and helps adolescents to establish autonomy as they make the transition to adulthood [19], some youth become excessively peer oriented, to the extent that they abandon family values and personal strengths to gain popularity [20]. Because young people value sexual activity as a sign of maturity [19], peer orientation may be a particularly powerful source of risk in this domain. Indeed, previous research has found peer orientation to be associated with risky sexual attitudes and behavior [21].…”
Section: Youth Mediatorsmentioning
confidence: 96%
“…It has been suggested that because peer acceptance is highly salient during adolescence, youth who are reliant on friends for validation of self-worth may be at greater risk [18]. Although moderate peer orientation is normative and helps adolescents to establish autonomy as they make the transition to adulthood [19], some youth become excessively peer oriented, to the extent that they abandon family values and personal strengths to gain popularity [20]. Because young people value sexual activity as a sign of maturity [19], peer orientation may be a particularly powerful source of risk in this domain.…”
Section: Youth Mediatorsmentioning
confidence: 98%
“…Other religious-involvement factors (e.g. service attendance and importance) have been studied in relation to alcohol, tobacco, and drug use (9,47,50,53,78,86,89,178) and adolescent sexual behavior and contraceptive use (7,26,136,155,164,174). Religious factors are associated with lower levels of behavioral risk such as alcohol use (2,45) and higher levels of health-promoting behaviors (e.g.…”
Section: Health and Lifestyle Behaviors And Health Care Utilizationmentioning
confidence: 99%
“…There is insufficient evidence to generalize our finding for either prosocial norms or spirituality as protective factors to other races/ethnicities. [152,46,100,138,[159][160][161][162][163][164][165][166][167][168][169][170][171][172][173] 12 c [38,153,161,163,167,174,175] [122,155,[188][189][190][191][192][193][194] 6 c [123,155,162,193,195] Use of contraception 2 a [196] 1 a [196] 9 ab [15,24,124,125,158,196] 4 c [56,…”
Section: Discussionmentioning
confidence: 99%